GAMBARAN FAKTOR RISIKO KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS KARANGKOBAR TAHUN 2022 - Bayu Suseno (Jurnal Ilmiah Medsains, 2023)
UPTD Karangkobar Health Center is one of the health centers in Banjarnegara Regency which still has ARI problems. Based on observations from January to March 2022, the prevalence of ARI is still quite high. The purpose of this study was to identify and describe the risk factors for acute respiratory infections (ARI) in children under five in the working area of UPTD Puskesmas Karangkobar. This research is included in descriptive research with cross sectional method. The population in this study were toddlers with ARI in the working area of UPTD Puskesmas Karangkobar who had checked themselves to the Puskesmas in the period January-March 2022, namely 60 toddlers with a random sampling technique. The data used in this study are primary data obtained from questionnaires and field observations and secondary data from the UPTD of Karangkobar Health Center. The results showed that most of the patients with ARI were male (51,7%). The highest toddler age is 2-5 years (76,7%). The highest BBL is normal BBL (96,7%). The most nutritional status is the good category (96,7%). Most of the immunization status is complete (98,3%). Most of the air pollution is still present (91,7%). Good ventilation is eligible (60%). The density of non-dense occupancy meets the requirements (71,7%). Humidity is not good (96,7%). The behavior of parents or family is very good (86%).The conclusion from the study of patients with ARI in infants who did not meet the requirements, namely the variables of air pollution and humidity. It is hoped that the community, especially caregivers of toddlers, will pay more attention to the conditions of the surrounding environment.